إنشاء المدن الذكية في الجزائر وضرورة التحول الرقمي: الرهان والتحديات؟ - أوكيل، محمد أمين; بودراهم، ليندة Boudarahem, Lindah (جامعة ابن خلدون تيارت, 2019)
The Algerian State has chosen the option of digitization as a basis to consolidate its path towards the creation of smart cities, it has adopted a development strategy aimed at modernizing the city by the establishment of a legal arsenal and devices special upgrades, As well as the development of digital capacities in new cities and the deployment of several modes of technology in urban areas. However, Algeria's recent experience in this regard still poses many digitization problems which prevent activating the requirements of the smart city, due to the lack of efficient electronic management, and to the low proportion of digital investments, While urban planning is not compatible with digitization.
تبنت الدولة الجزائرية خيار الرقمنة كسياسة محورية لتدعيم مسارها في إنشاء المدن الذكية، فانتهجت بذلك استراتيجية تنموية لعصرنة المدينة، تنبري من خلال استحداث ترسانة قانونية وأجهزة خاصة لترقيتها، إلى جانب تطوير القدرات الرقمية للمدن الجديدة، وبعث عدة وسائط للتكنولوجيا في المجال الحضري. غير أن حداثة التجربة الجزائرية في هذا الشأن، لازالت تطرح العديد من التحديات لتجسيد الرقمنة مما يحول دون تفعيل مقتضيات المدينة الذكية، ويظهر ذلك أساسا من خلال غياب إدارة إلكترونية فعالة، وتدني معدلات الاستثمارات الرقمية، فضلا عن عدم مسايرة التخطيط الحضري لمستجدات الرقمنة.
Keywords: المدن الذكية -- تكنولوجيا المعلومات -- الإدارة الإلكترونية -- تخطيط المدن